The Perspective Reviews: Relations of Language and Culture in English Language Teaching (ELT) - Hijriani Hijriani; Anilda Rosmala; Nelly Halim; Amaluddin Amaluddin (Universitas Muhammadiyah Enrekang, 2023)
This research is a literature study with descriptive qualitative research. Thus, this research used the Library Research Method, that research carried out using literature, either in the form of books, notes, or research reports from previous studies. In this literature study, the authors used various written sources such as articles, journals, and other relevant sources. The main source used by the author as the object of this research is an article entitled Language and Culture: research methods and approaches used in the multidisciplinary field of applied language, written by Claire Kramsch. Based on the analysis conducted by researchers, it can be concluded that culture is the inherited and innate set of ideas, attitudes, beliefs, values, and knowledge that is the general basis of social behavior.